ICT-Project-Based Learning on Cognitive and Psychomotor in Football Courses Learning Achievement - Okilanda, Ardo; Yendrizal, Yendrizal (Universitas PGRI Palembang, 2022)
The digital tools gave such alternative to make learning easier. Students got the opportunity to explore their knowledge while found by learning experience such tutoring and discussing. This study employed a quasi-experimental design with a non-equivalent post-test-only control group design. The results found t_cal= 2.90 and for t_table 5%= 2.00 and 1 % = 2.66. It means t_(ratio )> t_table. It concluded that there is a positive effect of using ICT-Project-Based Learning on cognitive and psychomotor in football courses learning achievement. Learning football using ICT-Project-Based Learning on cognitive and psychomotor in football courses through Zoom was interactive because students' easier to ask directly to lecturers so that increases theil learning achievements'. PBL integrated with ICT was successful to improve students' skills and achievement. PBL had a positive impact on student learning and procedures in learning.